Oathbreakers : the war of brothers that shattered an empire and made Medieval Europe - Gabriele, Matthew; Perry, David M., 1973- (Harper, an imprint of HarperCollins Publishers, 2024)
"The story of the Carolingian Civil War, a bloody, protracted battle pitting brother against brother, father against son, that would end an empire, upend a continent, and lay down the modern borders of Europe"--